Review of gas emissions from lithium-ion battery thermal runaway failure — Considering toxic and flammable compounds - Bugryniec, Peter J.; Resendiz, Erik G.; Nwophoke, Solomon M.; Khanna, Simran; James, Charles; Brown, Solomon F. (Journal of energy storage, 2024)
Lithium-ion batteries (LIBs) present fire, explosion and toxicity hazards through the release of flammable and noxious gases during rare thermal runaway (TR) events. This off-gas is the subject of active research within academia, however, there has been no comprehensive review on the topic. Hence, this work analyses the available literature data to determine how battery parameters affect the variation in off-gas volume and composition, to determine the flammability and toxicity hazards of different battery chemistries. It is found on average that: (1) NMC LIBs generate larger specific off-gas volumes than other chemistries; (2) prismatic cells tend to generate larger specific off-gas volumes than offer cell forms; (3) generally a higher SOC leads to greater specific gas volume generation; (4) LFP batteries show greater toxicity than NMC; (5) LFP is more toxic at lower SOC, while NMC is more toxic at higher SOC (respective to themselves); and (6) LFP off-gas has a greater flammability hazard. Further, recommendations are presented so that significant improvements in research can be made to advance the understanding of LIB off-gas further. Finally, this work is a critical resource to the battery community to aid the risk assessment of LIB TR fire, explosion and toxicity hazards. [Display omitted] •Comprehensive meta-analysis of Li-ion battery thermal runaway off-gas.•Specific off-gas production for various battery parameters presented.•Off-gas composition and toxicity analysed, compared between chemistries.•Recommendations for future research made to advance knowledge of off-gas.•Provides a critical resource for improving Li-ion battery risk assessments.